PNPLA3 rs738409 G allele carriers with genotype 1b HCV cirrhosis have lower viral load but develop liver failure at younger age - Senkerikova, Renata; Fraňková, Soňa; Jirsa, Milan; Kreidlová, Miluše; Merta, Dusan; Neroldova, Magdalena; Chmelová, Klára; Spicak, Julius; Sperl, Jan (PLoS One, 2019)
BACKGROUND: PNPLA3 rs738409 minor allele c.444G represents a risk factor for liver steatosis and fibrosis progression also in chronic hepatitis C (HCV). We investigated its impact on the timing of liver transplantation (LT) in patients with genotype 1b HCV cirrhosis. METHODS: We genotyped and evaluated 172 LT candidates with liver cirrhosis owing to chronic HCV infection, genotype 1b. One hundred patients needed LT for chronic liver failure (CLF) and 72 for a small hepatocellular carcinoma (HCC) in the cirrhotic liver without CLF. Population controls (n = 647) were selected from the Czech cross-sectional study MONICA. RESULTS: The CLF patients were younger (53.5 ± 7.2 vs. 59.6 ± 6.6, P < 0.001) with more advanced liver disease than HCC patients (Child-Pugh's score 9.1 ± 1.8 vs. 7.1 ± 1.9, P < 0.001, MELD 14.1 ± 3.9 vs. 11.1 ± 3.7, P < 0.001). PNPLA3 G allele increased the risk of LT for CLF in both allelic and recessive models (CG + GG vs. CC: OR, 1.90; 95% CI, 1.017-3.472, P = 0.045 and GG vs. CC + CG: OR, 2.94; 95% CI, 1.032-7.513, P = 0.042). Multivariate analysis identified younger age (P < 0.001) and the G allele (P < 0.05) as risk factors for CLF. The genotype frequencies between the CLF group and MONICA study significantly differed in both, allelic and recessive model (P = 0.004, OR 1.87, 95% CI 1.222-2.875; P < 0.001, OR 3.33, 95% CI 1.824-6.084, respectively). The OR values almost doubled in the recessive model compared with the allelic model suggesting the additive effect of allele G. In contrast, genotype frequencies in the HCC group were similar to the MONICA study in both models. Pretransplant viral load was significantly lower in GG than in CC + CG genotypes (median, IQR; 162,500 (61,550-319,000) IU/ml vs. 570,000 (172,000-1,595,000) IU/ml, P < 0.0009). CONCLUSIONS: Our results suggest that PNPLA3 rs738409 G allele carriage may be associated with a faster progression of HCV cirrhosis to chronic liver failure.
Keywords: alely; játra; nádory jater; Lipase; Membrane Proteins; Polymorphism, Single Nucleotide; Humans; Case-Control Studies; lidé středního věku; Hepatitis C, Chronic; jaterní cirhóza; studie případů a kontrol; jednonukleotidový polymorfismus; Female; Viral Load; Liver Failure; Carcinoma, Hepatocellular; Alleles; Genotype; lidé; Liver Cirrhosis; Liver Neoplasms; virová nálož; Liver Transplantation; transplantace jater; selhání jater; ženské pohlaví; chronická hepatitida C; Liver; Male; Middle Aged; Retrospective Studies; Genetic Predisposition to Disease; genetická predispozice k nemoci; Cross-Sectional Studies; membránové proteiny; genotyp; retrospektivní studie; mužské pohlaví; průřezové studie; lipasa; hepatocelulární karcinom